NUTRITIONAL STATUS OF OUTPATIENTS WITH TYPE 2 DIABETES AT QUANG NINH GENERAL HOSPITAL IN 2020-2021 (Vietnam Journal of Community Medicine, 2022)
Objective: Description of nutritional status of outpatients with type 2 diabetes treated in Quang NinhGeneral Hospital in 2020-2021.Method: A cross-sectional description was carried out on 457 outpatients with type 2 diabetes.Results: The majority (61.1%) of the study subjects were overweight (30.6%) and obese (30.5%);The prevalence of overweight in men (36.0%) was higher than that of women (24.0%), while therate of obesity in women (33.4%) was higher than that of men (28.1%). CED rate was only 1.3%.Prevalence of subjects with high waist circumference (male ≥90 cm, female ≥ 80 cm) was 50.1%; Thepercentage of women with high waist circumference (75.5%) was higher than that of men (29.6%).The majority of subjects had a normal VE/VM ratio, accounting for 67.6%; 32.4% of subjects hadhigh VE/VM ratio. In which, the high VE/VM ratio in women accounted for a higher rate of 70.6%while the high VE/VM ratio in men accounts for only 1.6%.
Keywords: Nutritional status, diabetes, Quang Ninh.